2021
DOI: 10.1186/s13023-021-01939-6
|View full text |Cite
|
Sign up to set email alerts
|

The long and winding road: perspectives of people and parents of children with mitochondrial conditions negotiating management after diagnosis

Abstract: Background The diagnostic odyssey for people with a rare disease is well known, but difficulties do not stop at diagnosis. Here we investigate the experience of people, or parents of children with a diagnosed mitochondrial respiratory chain disorder (MRCD) in the management of their disease. The work complements ongoing projects around implementation of consensus recommendations for management of people with MRCD. People with or caring for a child with a formally diagnosed MRCD were invited to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…Before the pandemic, this population was accustomed to overcoming challenges in accessing care and in day‐to‐day life. 38 As such, this community, both carers and people with GUaRD, was experienced in resilience and therefore we adopted this lens to interrogate the journals.…”
Section: Discussionmentioning
confidence: 99%
“…Before the pandemic, this population was accustomed to overcoming challenges in accessing care and in day‐to‐day life. 38 As such, this community, both carers and people with GUaRD, was experienced in resilience and therefore we adopted this lens to interrogate the journals.…”
Section: Discussionmentioning
confidence: 99%
“… 23 37 While the burden of disease for rare disorders may be similar to higher incidence conditions such as stroke or breast cancer, the added burden of the lack of a solid evidence base of effective treatments, best practice guidelines and competent and knowledgeable health service providers is not. The well-documented diagnostic odyssey for people with rare diseases 3 and laments that health professionals had never heard of their disease 4 is a burden unique to this group.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Access to appropriate specialist services, finding a generalist health provider who is willing to learn about the condition, living with uncertainty of what is best practice, and the trial and error nature of discovering it have all been reported. 4 Electronic resources, by which we mean mobile applications, websites, virtual monitoring devices, social media platforms, telehealth capability and online portals, hold promise of greater connectivity and collaboration in the field of rare diseases. Electronic resources are already being used to improve understandings of rare diseases as national and international online registries, 12 13 and virtual research consortiums 14 15 pool their data and consolidate findings.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to provide high-quality care are hampered by scarce research and medical knowledge (with sample sizes too low to run clinical trials for any individual disease), limited treatment options, and a lack of standardized guidelines for clinical management. For many rare diseases, health professionals may only see one case during their entire career [ 14 ].…”
Section: Introductionmentioning
confidence: 99%